Impact of Ease of Use, Usefulness, Attitude, and Trust on AI Adoption Intentions in Higher Education - Erwin Margatama; Galih Yudha Saputra; Celine Aloyshima Haris (TEPIAN, 2026)
The integration of Artificial Intelligence (AI) in higher education has attracted increasing attention, particularly in computer education. However, students’ acceptance of AI is influenced by several factors that require further investigation. This study aims to examine the effect of perceived ease of use, perceived usefulness, attitude, and trust on the utilization of AI in learning activities among computer education students. A quantitative approach was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with data collected from undergraduate students. The findings reveal that ease of use and usefulness significantly influence students’ attitudes toward AI, while trust plays a crucial role in shaping both attitudes and actual utilization. Furthermore, attitude is confirmed as a mediating variable that strengthens the relationship between ease of use, usefulness, trust, and the adoption of AI tools in learning. These results provide empirical support for the Technology Acceptance Model (TAM) and extend it by incorporating trust as an additional construct, offering new insights into AI adoption in higher education. The study highlights both theoretical contributions and practical implications for educators, particularly in the Indonesian context, to integrate AI effectively into learning environments.